Site-directed mutagenesis of newcastle disease VIRUS V protein in virus pathogenicity - Tham, May Ling (2021)
Newcastle disease virus (NDV) is an avian virus that is highly pathogenic in poultry causing severe economic losses during an outbreak. One of the virulence factors of NDV was identified as the V protein that antagonises the interferon of the host innate immunity in order to allow the virus to replicate successfully in the host cells. This protein is produced by RNA editing at the P gene through insertion of one guanine nucleotide at the conserved editing site. A conserved seven cysteine residues in the C-terminal of paramyxoviral V protein contributes to virus pathogenicity. However, no studies have been carried out to investigate the correlation between pathogenicity and the different lengths of the C-terminal of NDV V protein. This study aims to study the effect of V mutations on virus pathogenicity by mutating the V protein of AF2240-I, a local velogenic NDV strain. Site-directed mutagenesis was performed to introduce 396A>G399G>A at RNA editing site, and four premature stop codons: 456G>T, 537G>T, 624C>T and 642G>T in the V gene respectively. The NDV antigenome plasmids containing the mutated V genes were co-transfected with helper plasmids (plasmids containing NP, P, and L genes) into BSR T7/5 cells to produce the recombinant NDV (rNDV) by reverse genetics. The virus was then rescued and propagated in embryonated chicken eggs. Only three out of five rNDVs were successfully rescued. However, instead of having the substituted thymine in rNDV 456G>T, rNDV 624C>T and rNDV 642G>T, the thymine seemed to have mutated into cytosine. As a result, the stop codon was substituted with other amino acids and the V protein was no longer truncated. The viral pathogenicity was determined by mean death time (MDT) on 9-day old SPF embryonated chicken eggs. Results showed that rNDV 456G>T>C, rNDV 624C>T>C and rNDV 642G>T>C remained as mesogenic strains. It appears that an intact V protein is important for viral replication and pathogenicity. In conclusion, the pathogenicity of rNDVs were not reduced due to the substitution of the desired mutation into another nucleotide. This study warrants a further investigation on the mechanism of the viral RNA dependent RNA polymerase in introducing a mutation for successful virus replication.